Quebec Nurses’ Perceptions of the Integration of Sustainable Diet Promotion Into Clinical Appointments: A Qualitative Study - Larente-Marcotte, Stéphanie; Guillaumie, Laurence; Diallo, Thierno (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2022)
Introduction: A sustainable diet is a diet that is respectful of ecosystems, culturally acceptable, accessible and healthy. It is considered as a promising avenue for optimizing health and reducing the impacts of food on the environment. Several nursing associations have demonstrated a growing concern for nurses’ involvement in environmental and climate change issues, including in promoting sustainable diet. However, the literature reveals a lack of data on why and how nurses could address sustainable diet in their clinical practice.Objective: The aim of this study was to explore clinical nurses’ perceptions of their role in the promotion of sustainable diet.Methods: A descriptive qualitative study was conducted based on 6 focus groups involving 20 nurses from 7 regions of the province of Quebec, Canada. Computer-assisted thematic analysis was conducted on verbatim transcripts.Results: The discussions revealed 3 major themes. First, some dimensions of sustainable eating are already implicitly addressed and nurses were theoretically open to make further. However, it was difficult to see how nurses could translate this interest into concrete action due to a lack of time and their other clinical priorities. Lastly, in order to do this, nurses need support from health organizations as well as clear guidelines, training and tools.Discussion and conclusion: Despite experts’ recommendations, many barriers and inadequacies between experts’ recommendations and nurses’ reality prevent the implementation of concrete initiatives toward the promotion of sustainable diet among nurses. Nurses are invited to get involved and contribute to the promotion of sustainable diet with a “bottom-up” approach.